PENGARUH DISCHARGE PLANNING TERHADAP KECEMASAN PASIEN CORONARY ARTERY DESEASE (CAD) YANG DIRENCANAKAN AKAN MENJALANI TINDAKAN DIAGNOSTIK ANGIOGRAPHY KORONER DI INSTALASI RAWAT JALAN POLY JANTUNG RS. USU MEDAN - Suherni Suherni; Heni Triana (UNIVERSITAS SARI MUTIARA INDONESIA, 2020)
Coronary Angiography is an invasive examination to describe the condition of the coronary arteries of the heart by inserting a blood vessel catheter into the body and injecting contrast fluid to give a picture of coronary arteries on X-ray imaging immediately after contrast is injected. One of the things that nurses can do to reduce patient anxiety before undergoing a Coronary Angiography procedure is to application Discharge Planning . The purpose of this study was to determine whether there is an effect of application Discharge Planning on the anxiety of patients with coronary artery disease (CAD) who are planned to undergo diagnostic procedure by coronary angiography performed at an outpatient installation of cardiac polyclinic of the University of North Sumatra Hospital Medan. The present study was carried out with a quasi-experimental design by One The Group Test. The sample in this study was determined by consecutive sampling technique that produced 32 subjects as sample. The results of the study indicated by the statistical analysis of paired t-test that the average anxiety value of pre-test and post-test was 12,348% and the value of p was 0,000. This is also in accordance with the significance test (hypothesis) of the two groups where the value of t-counted of 12.50 is obtained compared to the value of t-table of 2.04. Thus it can be concluded that there are differences in anxiety before and after the intervention is given, in this case the intervention in question is the application Discharge Planning. It is recommended to nurses at the Outpatient Installation of Cardiac Polyclinic of the University of North Sumatra Hospital Medan to continue to application Discharge Planning related to the diagnostic procedures for coronary angiography that will be undertaken by the patient, as well as provide physiological and psychological support so that patients can undergo diagnostic procedures with optimistic, more relaxed, and without anxiety. Keywords: Coronary Angiography, Discharge Planning, Anxiety ABSTRAK Angiography Coronary adalah salah satu pemeriksaan invasif untuk menggambarkan keadaan arteri koroner jantung dengan cara memasukkan kateter pembuluh darah ke dalam tubuh dan menginjeksikan cairan kontras untuk memberikan gambaran pembuluh darah koroner pada pencitraan sinar-X segera setelah kontras diinjeksikan.. Salah satu hal yang dapat dilakukan perawat dalam mengurangi kecemasan pasien sebelum menjalani prosedur Angiography Coronary yaitu penerapan Discharge Planning. Tujuan penelitian ini adalah untuk mengetahui adanya pengaruh penerapan Discharge Planning terhadap kecemasan pasien Coroner Artery Desease (CAD) yang direncanakan akan menjalani tindakan diagnostic Angiografi Koroner yang dilaksanakan di Instalasi Rawat Jalan Poli Jantung Rumah Sakit Universitas Sumatera Utara Medan. Desain penelitian adalah desain Quasi Eksperimental dengan One The Group Test. Pengambilan sampel pada penelitian ini menggunakan Tehnik Consecutive Sampling yang berjumlah 32 orang. Hasil penelitian menunjukkan bahwa analisis dengan uji Statistik Paired T-Test diperoleh nilai rata-rata antara kecemasan pre dan post test adalah 12.438% dan p (value) adalah 0.000. Hal ini juga sesuai dengan nilai pengujian signifikan (hipotesis) dua kelompok diperoleh nilai t (hitung) adalah 11.50 dan t (table) adalah 2.04. Dengan demikian dapat disimpulkan bahwa terdapat perbedaan kecemasan sebelum dan sesudah diberikan intervensi, dalam hal ini intervensi yang dimaksud adalah penerapan Discharge Planning. Disarankan kepada perawat di Instalasi Rawat Jalan Poli Jantung RS. USU Medan untuk selalu tetap mempertahankan penerapan Discharge Planning terkait tindakan diagnostic Angiografi Koroner yang akan dijalani oleh pasien serta memberikan dukungan fisiologis maupun dukungan psikologis agar pasien dapat menjalani tindakan dengan optimis, lebih rileks, serta tanpa perasaan cemas